Glaucoma in diabetic patients and the need for further research - Salih, Omyma Abbas Banaga; Hamadani, Zaid Al; Alemrayat, Bayan; AlFehaidi, AlAnoud; Hamed, Ehab (International Journal of Research in Medical Sciences, 2020)
Glaucoma is considered the leading cause of irreversible blindness worldwide. Patients with diabetes are at risk of different eye complications, mainly retinopathy. Patients with diabetes are also at risk of developing cataract, uveitis and glaucoma. Three systematic reviews examined the associations between diabetes and glaucoma. Pooled analysis from those studies reported different OR 1.37, (95% CI=0.72-2.02), OR=1.36, (95% CI=1.25-1.50) and OR=1.48, (95% CI=1.29-1.71). Although the results seem close and suggest an increased risk in the diabetic population, the systematic reviews report significant heterogenicity and come short in explaining causality. Indeed, in one systematic review where 3 out of 7 studies suggested a non-significant association, the results were skewed to the positive side with a one-record based study that had a population size exceeding 2 million patients, while the rest of the studies had collectively 100 thousand patients. In our view, a case control study design that combines the patient surveys and electronic medical records ensure accurate data and more valid study results to validate or refute the association. This short communication article discusses the condition associations, theories for increased risk in the diabetic population and implications for future research.